Analisis Faktor-Faktor yang Membentuk Niat Penggunaan Berkelanjutan pada Pengguna Aplikasi Marketplace - Nofia Khoirunnisa; Wolor, Christian Wiradendi; Monoarfa, Terrylina Arvinta (Program Studi Administrasi Niaga STIA Said Perintah, 2024)
Advances in technology and internet access have made people more likely to make online purchases. This is also what drives the popularity of online shopping applications such as Shopee to increase the likelihood of users making purchases on an ongoing basis. In this situation, Shopee has the challenge of maintaining increased user sustainability by addressing several factors that are thought to have an impact on the sustainability of using the Shopee application. The purpose of this study is to identify the characteristics of Shopee application users, to analyze the behavior of Shopee application users, and to analyze what factors can shape the intention of continuous use in Shopee application users. This research uses a descriptive quantitative approach using a survey method. this research was analyzed using descriptive analysis techniques. In this study, descriptive analysis includes respondent profiles and data. In addition, in analyzing the data, this study uses the Exploratory Factor Analysis (EFA) analysis method approach using SPSS 30 software. The results of the study found that one main factor was formed that influenced the intention to continue using the Shopee application users in Jabodetabek. This factor is the intention to continue using the Shopee application. This factor reflects the dimensions of satisfaction, benefits, convenience, trust, and service performance perceived by users. This single factor is explained by an eigenvalue of 10.047 which explains 66.978% of the total variance which then influences their intention to continue using it.